Proposed program of music instruction for the elementary grades in the Division of Cagayan II - Tumaneng, Pepito A. 1939-
This study prepares a program of music instruction for the elementary grades in the division of Cagayan II based on the pupils' interests, experiences, and musical abilities. This study emphasizes the importance of providing music teachers guidelines in the formulation of objectives in music education, selection of appropriate musical activities, methods and procedures, teaching techniques and strategies in music teaching, and means of evaluating achievement in music education as well as the whole music program.